Kajian Teologi ‘Penebusan’ dalam Kitab Rut dan Implikasinya Pada Masa Kini - Miranda Br Ginting (Jurnal Arrabona, 2024)
Redemption is God's saving work for mankind. Redemption in the Old Testament leads us to one book that tells of redemption, namely the book of Ruth. This study uses a qualitative research method with a literature study approach, namely, the Bible against various data sources and texts that support and have a correlation with this research. The author examines the theology of redemption in the book of Ruth and its implications for today. Redemption in the book of Ruth shows the story of "the redemption of the family" which in Hebrew is called Go’el which means "one who redeems". The redemption in the Book of Ruth is the immediate family who has the right to deliver his relatives from misfortune. If you look at Boaz's redemption of Ruth, it shows that Boaz' redemption was not an element of compulsion, not an obligation or responsibility that Boaz had to do, but out of love. Likewise, God redeems not out of obligation, but love; not forced, but willing. Christ as Goel of believers today, like Boaz to Ruth. Christ's redemption for us He accepted us into His family and we became His children in the new creation.